Talent Development for Industry 4.0 - Karacay, Gaye (Springer International Publishing, 2017)
In today’s global environment, sustainability and competitive advantage of companies depend mostly on their capability of adaptation to changing business requirements. The Fourth Industrial Revolution, driving from the advancements in new digital technologies known collectively as Industry 4.0, has been profoundly changing dynamics of most industries. Automation of business processes together with emergence of novel business models impose new digital skill requirements for workforce. Creating future workforce involves not only attracting and developing new talent needed, but also re-skilling current employees through training programs as well as re-designing work processes for reducing the skill mismatch between jobs and employees. This chapter examines how Industry 4.0 will alter the landscape for talent development.